COMPARISON OF WEAR PERFORMANCE BETWEEN ALUMINA AND ALUMINA-ZIRCONIA CUTTING TOOLS AT HIGHER CUTTING SPEED - Hadzley, A.B.; Afuza, A.A.; Norfauzi, T.; Umar, U.A.A.; Herawan, S.G. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This study presented the comparison of alumina and alumina-zirconia cutting tools in machining with high feed rate application in terms of tool life and wear mechanism. Both cutting tools were prepared by the powder metallurgy processes including ball mill, cold isostatic press and sintering at the elevated temperature. These cutting tools were fabricated in the form of RNGN 120600 insert and machined with AISI 1045. The cutting parameters employed were 200-350 m/min cutting speeds with constant 0.175 mm/rev feed rate and 0.5 mm depth of cut. The results show that the alumina-zirconia cutting tool capable to machine AISI 1045 up to 164 seconds cutting time, which is almost five folds improvement as compared to alumina cutting tool which is at 36 seconds tool life. For alumina cutting tool, the wear mechanism demonstrated severe wear development at the concentrated area in the flank zone. This is due to the brittleness of material that makes it unable to resist load from the high feed rate impact. Whereas, alumina-zirconia cutting tool consistently demonstrated uniform wear development at the flank zone. The addition of zirconia enables the structure to be integrated strongly to resist high cutting load from the engagement of the cutting tool at the higher cutting speed.